Preparation and characterization of montmorillonite/brea gum nanocomposites films - Slavutsky, Anibal Marcelo (2013)
The aim of this study was the formulation and characterization of films, based on gum exudates from Brea tree and nanoclay particles, for food applications. Brea gum (BG) is a renewable resource available in semi-desert areas. Functional properties of brea gum based films were improved through the incorporation of montmorillonite (MMT). Studies on film forming solution of BG/MMT were conducted. Results indicated a reduction of foam forming with MMT incorporation due to the increase in surface energy. Nanoclay was incorporated to the polymer matrix and films were formed by casting. Effect of nanoclay concentration on physicochemical properties of films was studied. FTIR spectra showed a strong interaction between MMT and BG molecules and X-Ray diffractograms indicated an exfoliated MMT dispersion into film matrix. Optical properties of films were dependent on nanoclay concentration. Solubility and water and gas permeabilities decreased with increasing MMT content. Moisture sorption isotherms of BG and BG/MMT films were obtained. Results indicated that nanoclay incorporation produces a decrease in water uptake of BG. Nanoclay addition produced an increase in Young's module and tensile strength and a decrease in film elongation. Results showed that incorporation of 5% of MMT improved water resistance and water and gas barrier properties of BG based films and enhanced mechanical resistance of these films. Gas permeability measurements indicated that MMT addition reduced permselectivity (CO2/O2) of BG film.